Clinical Outcomes and Quantitative HBV Surface Antigen Levels in Diverse Chronic Hepatitis B Patients in Canada: A Retrospective Real-World Study of CHB in Canada (REVEAL-CANADA) - Carla S. Coffin; Sarah Haylock-Jacobs; Karen Doucette; Alnoor Ramji; Hin Hin Ko; David K. Wong; Magdy Elkhashab; Robert Bailey; Julia Uhanova; Gerald Minuk; Keith Tsoi; Alexander Wong; et al. (Viruses, 2022)
Background: Hepatitis B surface antigen (HBsAg) loss is associated with improved clinical outcomes for individuals with chronic hepatitis B (CHB); however, the effects of varying HBsAg levels on clinical outcomes in diverse cohorts are understudied. Methods: In this cross-sectional, multicentre, retrospective study, the data on adult subjects enrolled in the Canadian HBV Network with CHB seen from 1 January 2012 to 30 January 2021 with the treatment and virologic data within 1 year of HBsAg testing were analyzed. Patients were tested for HBsAg using qualitative (for HBsAg-negative samples) and/or commercial quantitative assays. Fibrosis or hepatic necroinflammation was determined by the liver stiffness measurement (LSM). The baseline data were summarized using descriptive statistics and compared by using univariable/multivariable analyses. Results: This study included 844 CHB patients, with a median age of 49.6 years (IQR 40.1–60.5), and 37% were female. In total, 751 patients (78.6%) had known ethnicity data, and 76.7% self-reported as Asian, 11.4% as Black, 6.8% as White, and 4.8% as other. Among the 844 patients, 237 (28.0%) were HBsAg (−) (<LLOQ), 190 (22.5%) had qHBsAg 1–100, 91 (10.8%) had qHBsAg 100–500, 54 (6.4%) had qHBsAg 500–1000, and 272 (32.2%) had qHBsAg >1000 IU/mL. Overall, 80% (682) had known HBeAg status at the last follow-up, and the majority (87.0%) were HBeAg-negative. In addition, 54% (461/844) had prior antiviral therapy, 19.7% of which (16.3, 23.7, n = 91) were HBsAg (−). The treated patients had a lower risk of cirrhosis (16.46, 95% CI 1.89–143.39, p = 0.01) or HCC (8.23, 95% CI 1.01–67.39, p = 0.05) than the untreated patients. A lower proportion of the HBsAg-loss group had cirrhosis (5.7% vs. 10.9%, p = 0.021) and HCC (0.9% vs. 6.2%, p = 0.001). Conclusion: In this retrospective, ethnically diverse cohort study, CHB patients who received antiviral therapy and/or had HBsAg loss were less likely to develop cirrhosis and HCC, confirming the results of the studies in less diverse cohorts. No association was found between the qHBsAg level and fibrosis determined with LSM. Individuals who achieved HBsAg loss had low-level qHBsAg within 1 year of seroclearance.